Topical NSAIDs for acute pain in adults. - Massey, T; Derry, S; Moore, R; McQuay, H (2010)
BACKGROUND: Use of topical NSAIDs to treat acute musculoskeletal conditions is widely accepted in some parts of the world, but not in others. Their main attraction is their potential to provide pain relief without associated systemic adverse events. OBJECTIVES: To review the evidence from randomised, double-blind, controlled trials on the efficacy and safety of topically applied NSAIDs in acute pain. SEARCH STRATEGY: We searched MEDLINE, EMBASE, The Cochrane Library, and our own in-house database to December 2009. We sought unpublished studies by asking personal contacts and searching on-line clinical trial registers and manufacturers web sites. SELECTION CRITERIA: We included randomised, double-blind, active or placebo (inert carrier)-controlled trials in which treatments were administered to adult patients with acute pain resulting from strains, sprains or sports or overuse-type injuries (twisted ankle, for instance). There had to be at least 10 participants in each treatment arm, with application of treatment at least once daily. DATA COLLECTION AND ANALYSIS: Two review authors independently assessed trial quality and validity, and extracted data. Numbers of participants achieving each outcome were used to calculate relative risk and numbers needed to treat (NNT) or harm (NNH) compared to placebo or other active treatment. MAIN RESULTS: Forty-seven studies were included; most compared topical NSAIDs in the form of a gel, spray, or cream with a similar placebo, with 3455 participants in the overall analysis of efficacy. For all topical NSAIDs combined, compared with placebo, the number needed to treat to benefit (NNT) for clinical success, equivalent to 50% pain relief, was 4.5 (3.9 to 5.3) for treatment periods of 6 to 14 days. Topical diclofenac, ibuprofen, ketoprofen, and piroxicam were of similar efficacy, but indomethacin and benzydamine were not significantly better than placebo. Local skin reactions were generally mild and transient, and did not differ from placebo. There were very few systemic adverse events or withdrawals due to adverse events. There were insufficient data to reliably compare individual topical NSAIDs with each other or the same oral NSAID. AUTHORS' CONCLUSIONS: Topical NSAIDs can provide good levels of pain relief, without the systemic adverse events associated with oral NSAIDs, when used to treat acute musculoskeletal conditions.